Feasibility of superior vena cava isolation in patients with cardiac implantable electronic devices. (27th October 2020) - Kataoka, Shohei; Ejima, Koichiro; Yazaki, Kyoichiro; Kanai, Miwa; Yagishita, Daigo; Shoda, Morio; Hagiwara, Nobuhisa
Abstract: Introduction: Some patients with cardiac implantable electronic devices (CIEDs) require atrial fibrillation (AF) ablation, and the superior vena cava (SVC) has been identified as one of the most common non‐pulmonary vein foci of AF. This study aimed to investigate the interaction between SVC isolation (SVCI) and CIED leads implanted through the SVC. Methods and Results: We studied 34 patients with CIEDs who had undergone SVCI as part of AF ablation (CIED group), involving a total of 71 CIED leads. A similar number of age‐, sex‐, and AF type‐matched patients without CIEDs formed a control group (non‐CIED group). Patients' background and procedural characteristics were compared between the groups. In the CIED group, lead parameters before and after AF ablation were compared, and lead failure after AF ablation was also examined in detail. Procedural characteristics other than fluoroscopic time were similar in both groups. The success rate of SVCI after the final ablation procedure was 91.2% in the CIED group and 100% in the non‐CIED group; however, these differences were not statistically significant. Lead parameters before and after the AF ablation did not significantly differ between the two groups. Lead failure was observed in three patients, with a sensing noise in one patient and an impedance increase in two patients after SVCI. Conclusion: SVCI was achievable without lead failure and significant change in lead parameters in most patients with CIEDs; however, it should be noted that lead failure was observed in 8.8% of the study patients after SVCI.